Cellulose nanocrystals into Poly(ethyl methacrylate) used for dental application - Leite, Andressa [UNESP] (2022)
Cellulose nanocrystals (CNCs) can improve the mechanical properties of dental resins. However, there is a deficiency of information about the behavior of physical properties of resins after this addition. The purpose was to evaluate the characterization and physical properties of hard chairside reline material modified with CNCs (0.25%, 0.5%, 0.75% or, 1.0%). Addition of CNCs at 0.5%, 0.75% and 1% increased Vickers hardness; 0.75% decrease surface free energy; 0.75% and 1% showed similar to control on the surface roughness. The simple and straightforward approach of adding CNCs, a renewable material, provides good potential for its future practical application as it has shown promise with increasing hardness. It means that the incorporation of CNCs into this denture reline resin could improve the abrasion resistance of this material, which is desirable in the long term.